Ali lahko s pomočjo aktivnih videoiger vplivamo na gibalno učinkovitost? - Šlosar, Luka (Revija za elementarno izobraževanje, 2016)
The Potential of Active Video Games (AVG) to Improve Motor Efficiency. The growing interest in video games and the related increase in sedentary lifestyles among adolescents has encouraged researchers to look for alternative strategies replacing the passive time in front of the screen with the active one. The solution was found in active video games (AVG), which require physical activity from the player. Given encouraging results about the impact of AVG on healthy lifestyle, subsequent studies were expanded to cover the area of motor abilities and sports performance. The purpose of our article is to determine whether the use of AVG can improve sport performance, bring progress in sports and rehabilitation.